Analisis Kuantitatif Pendapatan Pajak Reklame terhadap Pendapatan Asli Daerah Pemerintah Daerah Kota Tasikmalaya di Dinas Pendapatan Kota Tasikmalaya - Budi Lesmana; Riri Rumaiza (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2019)
The title of this research is “Quantitative Analysis Earnings of Advertising Tax towards Regional Ordinary Earning Goverment Regional Tasikmalaya City in Dinas Pendapatan kota Tasikmalaya”. Dinas pendapatan (DIPENDA) kota Tasikmalaya is one Institution of Geverment moving to muster Regional Ordinary Earnings in Tasikmalaya city. One type from Regional Ordinary Earning Tasikmalaya city is Advertising Tax. This research aim to know how percentage of earnings advertising tax towards regional ordinary earning gevernment regional Tasikmalaya city in Dinas pendapatan kota Tasikmalaya and ti know how of tax worker do observation. Method of research used by method of Deskriptive Ratio. Having taken steps analyze and the problem solution,writer get conslusion that percentage earnings of advertising tax towars regoinal ordinary earning goverment 0.736%. while effort ti increase observation among tax workw=er to tax prayer that is improve observation process throught monitoring,observation and operation for as diametrical as collection prosess, apply more coherent sanction to tax-dodger and to worker which impinge regulation of according to invitation going into effect, improve sercice to tax payer, give socialization to tax payer, arrange in order advertising which not yet paying tax of its advertising, make –up of quality of SDM in Dinas Pendapatan Kota Tasikmlaya.